Endotoxin, ammonia, and total and respirable dust in swine confinement buildings: the effect of recirculated air and respiratory protective masks - J A Pickrell; A J Heber; James P Murphy; M M May; D Nolan; F W Oehme; D Schoneweis; J R Gillespie; Steven C Henry (Kansas Agricultural Experiment Station Research Reports, 1992)
Caretakers and pigs in dusty environments with particles and toxic gases may sustain health consequences. We studied concentrations of ammonia, endotoxin, and total and respirable dust particles in four mechanically ventilated swine nurseries and two grower facilities using an ammonia sampler, filter, and British cyclone. In two of the nursery facilities, we determined the protection offered by respiratory masks that were mounted on glass funnels with filters or British cyclones and sampled for dust. In response to the increasing summer ventilation, large, nonrespirable particle concentrations in swine building atmospheres were reduced more completely by ventilation air movement than smaller respirable particles or ammonia. Total airborne endotoxin concentrations were similar to those eliciting pulmonary reactions. Total airborne endotoxin correlated with total suspended particles rather than respirable particles. Smaller respirable fecal particles enriched in endotoxin apparently stick to larger nonrespirable particles or are agglomerated before they became airborne. Internal recirculated air partially limited the mass concentration of respirable particles in the breathing zone of swine caretakers at lower but not higher ventilation rates. Respiratory protection limited the potential total dust exposures of swine caretakers in such atmospheres (<25>%, 2-tie masks;<50%, I-tie masks of the total suspended particles). Respirable particles were reduced to<55% by 2-tie masks. Properly worn 2-tie masks protect against both large and small respirable particles in swine confinement facilities.; Swine Day, Manhattan, KS, November 19, 1992
Keywords: Swine day; 1992; Kansas Agricultural Experiment Station contribution; no. 93-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 667; Swine; Dust; Respirable dust; Endotoxin; Recirculated Air; Respiratory protective masks